2018
DOI: 10.1128/mbio.01114-18
|View full text |Cite
|
Sign up to set email alerts
|

Monoassociation with Lactobacillus plantarum Disrupts Intestinal Homeostasis in Adult Drosophila melanogaster

Abstract: Adult Drosophila melanogaster raised in the absence of symbiotic bacteria have fewer intestinal stem cell divisions and a longer life span than their conventionally reared counterparts. However, we do not know if increased stem cell divisions are essential for symbiont-dependent regulation of longevity. To determine if individual symbionts cause aging-dependent death in Drosophila, we examined the impacts of common symbionts on host longevity. We found that monoassociation of adult Drosophila with Lactobacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…The comparison of life history traits in wild flies bearing either A. tropicalis or L. fructivorans showed that altering the microbial community can mask host genotype, but should not be interpreted that all AABs or LABs confer life history traits of the same magnitude. Numerous studies of traits in monoassociated Drosophila reinforce the expectation that the microbial influences are species-specific and possibly even strain-specific (58-60, 64, 67, 102, 108-111). Further research is required to elucidate the underlying mechanisms, and to establish the extent to which the impact of individual microbial taxa on host life history traits in monoassociations (as used in these experiments), or controlled multi-species associations (112) may be displayed in the taxonomically diverse microbial communities in natural fly populations.…”
Section: Discussionmentioning
confidence: 86%
“…The comparison of life history traits in wild flies bearing either A. tropicalis or L. fructivorans showed that altering the microbial community can mask host genotype, but should not be interpreted that all AABs or LABs confer life history traits of the same magnitude. Numerous studies of traits in monoassociated Drosophila reinforce the expectation that the microbial influences are species-specific and possibly even strain-specific (58-60, 64, 67, 102, 108-111). Further research is required to elucidate the underlying mechanisms, and to establish the extent to which the impact of individual microbial taxa on host life history traits in monoassociations (as used in these experiments), or controlled multi-species associations (112) may be displayed in the taxonomically diverse microbial communities in natural fly populations.…”
Section: Discussionmentioning
confidence: 86%
“…ROS production in this interaction requires lactate oxidation by the host intestinal lactate dehydrogenase, suggesting that changes in host gene expression can modulate the influence of the microbiota on tissue homeostasis (86). A second study reported that mono-association with L. plantarum disrupts intestinal homeostasis and shortens life span, confirming the deleterious effects of excessive or unbalanced colonization with normally beneficial bacteria (87).…”
Section: Epithelial Immunity In Drosophila and The Microbiotamentioning
confidence: 98%
“…One explanation for why interactions between Ap and the T6SS are not sufficient to inhibit proliferation comes from the effect of Ap mono-association on IPCs. Ap promotes growth and renewal of the intestinal epithelium (Fast et al, 2018b). As it is highly unlikely that V. cholerae targets each Ap bacterium in a mono-associated gut, it is possible a portion of Ap promotes IPC proliferation despite the generation of putative pathogenic signals from T6SS-Ap interactions.…”
Section: T6ss Suppression Of Epithelial Renewal Requires Higher-ordermentioning
confidence: 99%
“…Lactobacillus plantarum KP (DDBJ/EMBL/GenBank chromosome 1 accession CP013749 and plasmids 1-3 for accession numbers CP013750, CP013751, and CP013752, respectively), Lactobacillus brevis EF (DDBJ/EMBL/GeneBank accession LPXV00000000), and Acetobacter pasteurianus AD (DDBJ/EMBL/GeneBank accession LPWU00000000). Lactobacillus plantarum KP, Lactobacillus brevis EF, and Acetobacter pasteurianus AD have previously been described (Fast et al, 2018b;Petkau et al, 2016).…”
Section: Bacterial Stocksmentioning
confidence: 99%